Time-Temperature and Time-Stress Correspondence in Non-Linear Creep-Experimental Amorphous Polymer Behaviour and Quantitative Modelling Approaches - André, José Reinas (2004)
Non-linear creep is described by a non-simulative, analytical, dynamic molecular modelling approach. Elementary, molecular-scale, process-relevant frequencies are derived by adequate kinetic formulation. They follow almost exactly an Arrhenius-like behaviour with a range of activation enthalpies. Their relative contribution to the overall macroscopic behaviour of the materials is quantified to account for the materials’ retardation time spectra and final non-Arrhenius behaviour. A new creep compliance equation is derived, yielding a fully coupled timetemperature-stress formulation, with long-term predictive capability. Experimental data for poly(methyl methacrylate) are analysed to identify the extent to which timetemperature and time-stress correspondence relationships may be valid, and it is shown that they are approximations (especially the latter), limited to narrow ranges of experimental variables, in contrast to the proposed model, which more reasonably fits the experimental behaviour